ANALISIS DISKRIMINAN TERHADAP PEMBELIAN TAK TERENCANA PADA RITEL MODERN YANG DILAKUKAN MAHASISWA (Studi Kasus Pada Carrefour Dan Hypermart Palembang) - Suhartini Karim; Aslamia Rosa (JEMBATAN, 2012)
ABSTRACT This research was held to reveal whether Impulsive Buying at Carrefour and Hypermart in Palembang are different or not, and whether there are any different influence to Impulsive Buying by among variables merchandise, price, promotion and retail atmosphere. The research was conducted in Carrefour in Palembang Square and Hypermart in Palembang Square Extension, where both these modern retails are located on two adjacent buildings. The calculation results indicate that discriminant Impulsive Buying in both the retail is not different. Also merchandise, pricing, promotions and atmosphere influence Impulsif Buying in both the retail is not different. Keywords : Discriminant Analysis, Impulsive Buying, Merchandise, Price, Promotion, Retail Atmosphere